Two new earthworm species (Oligochaeta, Megascolecidae) from An Giang province, Vietnam - Tung, Nguyen Thanh (Academia Journal of Biology, 2016)
Two new earthworm species are described from An Giang Province, southern Vietnam. Metaphire nhuongi sp. nov. is distinguished from its congeners by having four pairs of spermathecal pores in lateroventral intersegments 5/6/7/8/9, and two pairs of genital markings in 17/18 and 18/19. Polypheretima alba sp. nov. is recognized by multiple spermathecal pores in dorsal intersegments 4/5/6/7, genital markings 4-6 pairs on xix-xxiii, and body whitish. Received 2 November 2016, accepted 7 December 2016, published online 8 December 2016